Estado de madurez de Bracharia decumbens y la producción de metano in vitro (2019)
Abstract The livestock activity is questioned by the production of greenhouse gases (GHG) and mainly for the contribution of methane of enteric origin. Methane production per unit of ingested dry matter increases when animals are fed low quality forages. The use of low quality forages to feed ruminants not only contributes to global warming but also implies a lower productivity due to the loss of ingested energy in the form of methane and in the feces. Improving forage quality (decrease of fiber and increase of protein) reduce methane production per unit of fermented organic matter due to modifications in the metabolic pathways of fermentation. In the Araucan piedmont, the main forage is Brachiaria spp and most of the livestock farms use Brachiaria decumbens. The number of live leaves per tiller has been suggested as a way to determine the degree of maturity of pastures. In B. decumbens, the appearance of the fifth leave causes the first leave to begin its senescence. To determine the effect of harvesting B. decumbens pastures with 3, 4, or 5, green leaves per tiller on nutritional quality, in vitro fermentation and methane production patterns, nine plots (4x5 m) were assigned to three treatments of harvest (3, 4 or 5 leaves per tiller) at random. Each plot was harvested according to the number of leaves per tiller twice after a uniform cut. Nutritional composition was determined and fermentation were carried out in vitro for 24 ha each of the materials harvested in each plot. For the analysis of the data of the variables of nutritional quality and minerals, an ANAVA was used with repeated measures in time (two cuts) and three treatments (3, 4, 5 leaves per tiller) and three repetitions (plots ). Increasing the number of leaves per tiller increased the amount of NDF (62.4 vs. 66.1%), FDA (30.7 vs. 32.5%), LG (1, 6 vs. 1.9%), while reducing PC (15 vs. 7.7%) and digestibility (64 vs 51%) (p <0.05).The mineral composition did not vary due to the time of harvest except for Fe, P, Na which decreased as the number of leaves per tiller increased (p< 0.05).Gas production was higher for immature (3 and 4 leaves) than for more mature (5 leaves) on the fisrt cut (p<0,05) but not in the second. For the analysis of gas production, methane production and AGV, the ruminal fluid factor was added to the model used, it was added this factor performing an analysis of variance (ANAVA) of repeated measures of three factors: treatments (3, 4 and 5 leaves per tiller), rumen fluid (1, 2, 3, 4) and the cut (1 and 2). Methane production per unit incubated DM was higher for harvested for pasture with leaves 3 and 4 than for 5 leaves (p< 0.05), but the methane per gram of MSD and FDNd was similar (p> 0.05).The digestibility of the fiber was higher for pastures harvested with 3 and 4 leaves than with 5 leaves (p <0.05). Harvesting pastures of B. decumbens with fewer leaves per tiller increases nutrient concentration and digestibility without modifying methane production per unit of degraded dry matter. Keywords: gas technique, fermentation, pastures, killer, in vitro.